1995
DOI: 10.1007/bf02065533
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel bacterial overgrowth in patients with alcoholic cirrhosis

Abstract: A total of 89 patients with alcoholic cirrhosis and 40 healthy subjects were included in a study to assess the prevalence of intestinal bacterial overgrowth and to analyze its relationship with the severity of liver dysfunction, presence of ascites, and development of spontaneous bacterial peritonitis (SBP). Bacterial overgrowth was measured by means of a breath test after ingestion of glucose. Intestinal bacterial overgrowth was documented in 27 (30.3%) of the 89 patients with alcoholic cirrhosis and in none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 22 publications
4
41
3
Order By: Relevance
“…Moreover, these figures are in agreement with previous published results using our criteria which have shown that the 50 g D -glucose BH 2 T has a sensitivity range of 67–93% and a specificity range of 78–100% for the diagnosis of SIBO [26,27,28]. An elevated fasting BH 2 T concentration is considered by some teams associated with SIBO [3, 5, 6]. Fasting BH 2 concentrations depend on the amount of carbohydrates, glycoproteins and at a lesser degree proteins delivered to the colonic flora under fasting conditions: this amount may be increased in patients with cirrhosis because of delayed intestinal transit, protein-losing enteropathy or hemorrhage, conditions associated with malabsorption other than SIBO (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Moreover, these figures are in agreement with previous published results using our criteria which have shown that the 50 g D -glucose BH 2 T has a sensitivity range of 67–93% and a specificity range of 78–100% for the diagnosis of SIBO [26,27,28]. An elevated fasting BH 2 T concentration is considered by some teams associated with SIBO [3, 5, 6]. Fasting BH 2 concentrations depend on the amount of carbohydrates, glycoproteins and at a lesser degree proteins delivered to the colonic flora under fasting conditions: this amount may be increased in patients with cirrhosis because of delayed intestinal transit, protein-losing enteropathy or hemorrhage, conditions associated with malabsorption other than SIBO (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Reasons for the high prevalence of SIBO in patients with cirrhosis include spontaneous or drug-induced hypochlorhydria [5], spontaneous or drug-induced intestinal dysmotility [2] and severity of cirrhosis [4, 6]. More recently, Morencos et al [6] have shown that SIBO diagnosed by BH 2 T occurred in cirrhotics particularly when ascites was present (37% in patients with ascites vs. 5% in patients without ascites).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations